The importance of social media in the citizens'life of the city of Currais Novos/RN (Research, Society and Development, 2019)
The present work aims to discuss the importance of social media in the life of individuals in the city of Currais Novos / RN, which was conducted with five interviewees from different age groups, between fourteen and sixty years of age. The methodology used is of a qualitative nature, based on a telematized study carried out with subjects of different ages. Data collection took place through an interview. As a result the study shows that individuals have become dependent on social media and its functionalities, whether at work or in the interaction between subjects, media are essential in their lives. Finally, the study points out that social media significantly influence the lives of individuals in the city of Currais Novos / RN, as they enable interaction and communication, impacting in a relevant way in the daily life of these subjects.